The golden age of arthropods: ancient mechanisms of colour production in body scales. Issue 159 (2nd October 2019) - D'Alba, Liliana; Wang, Bo; Vanthournout, Bram; Shawkey, Matthew D.
Abstract : Insect colour is extremely diverse and produced by a large number of pigmentary and nanostructural mechanisms. Considerable research has been dedicated to these optical mechanisms, with most of it focused on chromatic colours, such as blues and greens, and less on achromatic colours like white and gold. Moreover, studies on the evolution of these colours are less common and largely limited to inferences from extant organisms, in part because of the limited amount and types of available fossil material. Here, we directly compare nanostructure and colour of extant and amber-preserved (approx. 15 and 99 Myr old, respectively) gold-coloured representatives of micromoths (Lepidoptera: Micropterigidae) and springtails (Collembola: Tomoceridae). Using electron microscopy, microspectrophotometry and finite domain time difference optical modelling, we show that golden coloration in the extant micromoth is produced by nanometre-scale crossribs that function as zero-order diffraction gratings and in the springtail by a diffraction grating without crossribs. Surprisingly, nanostructure and thus predicted colour of the amber-preserved specimens were nearly identical to those of their extant counterparts. Removal of amber enabled direct colour measurement of the fossil micromoth and further revealed that its colour matched both that of the extant specimen and the predicted colour, providing further support for our optical models. Our data thus clearly show an early origin and striking conservation of scale nanostructures and golden coloration, suggesting strong selection pressure either on the colour itself or on the mechanisms that produce the colour. Furthermore, we show the thus-far untapped potential for the use of amber-preserved specimens in studies on the evolution of organismal coloration.